First World Consensus Conference on pancreas transplantation: Part II – recommendations. Issue Volume 21:Issue S3(2021)Supplement (29th July 2021) - Boggi, Ugo; Vistoli, Fabio; Andres, Axel; Arbogast, Helmut P.; Badet, Lionel; Baronti, Walter; Bartlett, Stephen T.; Benedetti, Enrico; Branchereau, Julien; Burke, George W.; Buron, Fanny; Caldara, Rossana; et al.
Abstract : The First World Consensus Conference on Pancreas Transplantation provided 49 jury deliberations regarding the impact of pancreas transplantation on the treatment of diabetic patients, and 110 experts' recommendations for the practice of pancreas transplantation. The main message from this consensus conference is that both simultaneous pancreas‐kidney transplantation (SPK) and pancreas transplantation alone can improve long‐term patient survival, and all types of pancreas transplantation dramatically improve the quality of life of recipients. Pancreas transplantation may also improve the course of chronic complications of diabetes, depending on their severity. Therefore, the advantages of pancreas transplantation appear to clearly surpass potential disadvantages. Pancreas after kidney transplantation increases the risk of mortality only in the early period after transplantation, but is associated with improved life expectancy thereafter. Additionally, preemptive SPK, when compared to SPK performed in patients undergoing dialysis, appears to be associated with improved outcomes. Time on dialysis has negative prognostic implications in SPK recipients. Increased long‐term survival, improvement in the course of diabetic complications, and amelioration of quality of life justify preferential allocation of kidney grafts to SPK recipients. Audience discussions and live voting are available online at the following URL address: http://mediaeventi.unipi.it/category/1st‐world‐consensus‐conference‐of‐pancreas‐transplantation/246 . Abstract : This article described how pancreas transplantation impacts on life expectancy, quality of life, and course of diabetic complications based on the jury deliberations and expert recommendations from the First World Consensus Conference on Pancreas Transplantation.